The Effectiveness of Production-Based Learning Models in the ICARE Approach to Entrepreneurial Literacy Ability - Suminar, Tri; Arbarini, Mintarsih; Shofwan, Imam; Setyawan, Novi (Journal of Nonformal Education, 2021)
Entrepreneurship training activities in the literacy village program are one of the national literacy movement programs. Learning citizens with limited characteristics need effective learning skills to achieve the goals of literacy skills in the industrial era 4.0. The purpose of this study was to test the effectiveness of the Production Based Training learning model with the ICARE approach on entrepreneurial literacy skills of women participating in entrepreneurship training in literacy villages. The research method used is a quantitative approach pretest-posttest one group design with data analysis using SPSS t-test. The research population is the community of women as learning citizens in the literacy village program. The sampling technique was simple random sampling. Data collection techniques used observation, questionnaires, and performance ability tests. The results showed that the ICARE-based Production-Based Training learning model was effective in improving entrepreneurial literacy skills significantly as indicated by the high insight into entrepreneurial knowledge and attitudes as well as pioneering entrepreneurial skills with critical thinking skills, communicating, collaborating, and developing creativity in problem-solving to pioneer entrepreneurship. The impact of this research is to provide increased literacy skills, especially for marginalized women in pioneering and developing entrepreneurship.